The Nordic market for selected products of export interest to developing countries - International Trade Centre UNCTAD/GATT. (Geneva : International Trade Centre UNCTAD/GATT, 1970)
The book attempt to supply market information in respect of the four Nordic countries on selected product groups, exports of which are of interest to many developing countries, and to give basic guidance for approaching these markets.
usc 29/01/2019
Loans
Keywords: Market surveys; Export marketing; Commerce; Developing countries; Scandinavia